Journal of Pediatric Nursing: Nursing Care of Children and Families Vol.26 Issue 1, February 2011 Editor, Cecily Lynn Betz - Redaksi (Elsevier, 2011)
-Comparison of arm and calf automatic noninvasive blood pressures in pediatric intensive care petients -Ensuring children eat a healthy diet: a theory-driven focus group study to inform communication aimed at parents -Asthms: a health dispary among African children: the impact and implications for pediatric nurses - ....